Writing fiction; a phenomenological study of the creative writing experience of fiction writers - Konstantinos Mavrakakis; Abigail Chipman (Modern Psychological Studies, 2023)
While the focus of previous psychological research on artistic creativity has been mainly cognitive, the phenomenology of creativity has been largely neglected. This research aimed to address this gap, exploring how fiction writers experience the creative writing process. Two semi-structured interviews were carried out with published fiction writers. A thematic analysis of these interviews was conducted in order to explore how writers experience the creative writing process. The three common emergent themes that were selected for analysis were firstly, finding your voice, secondly, living between two worlds, and thirdly, facing the challenges of writing. This study generated insight into the creative writing experience of fiction writers.